A Study of Epitaxial Growth of Gan And Ingan/Gan Heterostructure on A-Plane Sapphire Substrates: Investigating the Optimization of Epitaxial Growth of GaN on A-plane Sapphire Substrates (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Group-III nitride-based semiconductors have shown promising promise as the foundation for anew generation of optoelectronic, high-temperature, and high-power microelectronic devices. Due to thehigh cost of GaN templates and the difficulty of growing GaN single crystals, this material is typicallygrown heteroepitaxially on incompatible substrates such as Al2O3, SiC, Si, etc. Even if the crystal qualityof epitaxial layers has vastly improved thanks to developments in growth technology, there is still anissue with the considerable discrepancy in lattice constants and thermal expansion coefficients betweenthe epitaxial layer and the substrate. C-plane (0001) sapphire has been the primary focus of research onsubstrates that can support the growth of high-quality epitaxial GaN films. The substantial mismatchbetween the lattice (14) and thermal expansion coefficient (56), which has hindered the nucleationand growth of epitaxial GaN, has prompted the development of a number of strategies for optimizingthese processes. High densities of different crystallographic defects, like dislocations and domainborders, etc., impede the growth of GaN on c-plane sapphire. In contrast, a-plane sapphire substrateshave been reported in the literature as a replacement for c-plane sapphire substrates due to the smallerlattice mismatches between [0002] GaN parallel to [1120] sapphire and [1100] GaN parallel to [1100]sapphire. A decrease in lattice mismatch will allow for the formation of GaN with higher crystallinequality, fewer flaws, and hence superior devices. Growth of GaN films on a-plane sapphire with earlynitridation and low temperature GaN buffer layers results in smooth surface morphology. The influenceof trap states, centers for radiative and non-radiative recombination in the material, must be taken intoaccount in addition to smooth surface morphology and crystalline quality, both of which areprerequisites for device competent semiconductor material. The impact of GaN and AlN buffer layers onGaN development on a-plane sapphire has also been investigated.